The Recombinant Expression Proteins FnBP and ClfA From Staphylococcus aureus in Addition to GapC and Sip From Streptococcus agalactiae Can Protect BALB/c Mice From Bacterial Infection - Ma, Zhongchen; Yin, Xinyue; Wu, Peng; Hu, Ruirui; Wang, Yong; Yi, Jihai; Wang, Zhen; Chen, Chuangfu (Frontiers in Veterinary Science, 2021)
Dairy cow mastitis is a serious disease that is mainly caused by intramammary infection with Staphylococcus aureus and Streptococcus agalactiae (GBS). FnBP and ClfA are the virulence factors of Staphylococcus aureus, while GapC is the respective factor for Streptococcus agalactiae. Sip is a highly immunogenic protein and that it is conserved in all GBS serotypes. In this study, we analyzed the abovementioned four genes prepared a FnBP+ClfA chimeric protein (FC), a GapC+Sip chimeric protein (GS), and a FnBP+ClfA+GapC+Sip chimeric protein (FCGS) based on the antigenic sites to evaluate their use in vaccine development. After expression and purification of the recombinant proteins in E. coli, BALB/c mice were immunized with them to examine resistance effects. The total lethal and half lethal doses of S. aureus and S. agalactiae were then measured and the immunoprotective effects of the fusion proteins were evaluated. The FC and FCGS chimeric proteins could induce mice to produce high levels of antibodies and bacterial loads were significantly reduced in the spleens and livers after challenge. After immunization with FCGS, the recipients resisted the attacks of both S. aureus and S. agalactia, indicating the potential of the fusion protein as a mastitis vaccine.